Mixed logit models and network formation. (19th December 2022) - Gupta, Harsh; Porter, Mason A
Abstract: The study of network formation is pervasive in economics, sociology, and many other fields. In this article, we model network formation as a 'choice' that is made by nodes of a network to connect to other nodes. We study these 'choices' using discrete-choice models, in which agents choose between two or more discrete alternatives. We employ the 'repeated-choice' (RC) model to study network formation. We argue that the RC model overcomes important limitations of the multinomial logit (MNL) model, which gives one framework for studying network formation, and that it is well-suited to study network formation. We also illustrate how to use the RC model to accurately study network formation using both synthetic and real-world networks. Using edge-independent synthetic networks, we also compare the performance of the MNL model and the RC model. We find that the RC model estimates the data-generation process of our synthetic networks more accurately than the MNL model. Using a patent citation network, which forms sequentially, we present a case study of a qualitatively interesting scenario—the fact that new patents are more likely to cite older, more cited, and similar patents—for which employing the RC model yields interesting insights.